2017
DOI: 10.22373/share.v6i2.1530
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Adoption of Good Governance: Evidences From Zakat Institutions in Padang, Indonesia

Abstract: Zakat is one of the fundamental principles of Islam and central to develop an economic system by enhancing socio-economic development. The importance of proper management and governance are challenges for these institutions. This study examined the determinants of the adoption of good governance practices in Zakat institutions in Padang, Indonesia. A total of 51 questionnaires were analyzed out of 135 that had been distributed. The data were analyzed using the Statistical Package for the Social Science (SPSS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
0
10
0
3
Order By: Relevance
“…This direct correlation between subjective norms on the behavior of obedience and paying zakat shows that the perception of the surrounding environment of muzakki has an impact on the final decision of muzakki to pay zakat through zakat management organization. The expectations of people in the muzakki environment are indicators that dominate subjective norms (Wahyuni, 2017;Zagrali, 2017).…”
Section: Subjective Norms Toward Behavior and Intentionmentioning
confidence: 99%
“…This direct correlation between subjective norms on the behavior of obedience and paying zakat shows that the perception of the surrounding environment of muzakki has an impact on the final decision of muzakki to pay zakat through zakat management organization. The expectations of people in the muzakki environment are indicators that dominate subjective norms (Wahyuni, 2017;Zagrali, 2017).…”
Section: Subjective Norms Toward Behavior and Intentionmentioning
confidence: 99%
“…GCG research has revealed the factors contributing to GCG implementation: transparency, accountability, responsibility, independence, fairness, and shariah compliance (Firmansyah & Devi, 2017;Permana & Baehaqi, 2018;Tahliani, 2018). The other factors influencing the GCG implementation are technology utilization, quality management (Suryandari F, 2015), and the institution's size (Wahyuni TD, 2017). Other research on GCG was conducted by Mubtadi & Susilowati (2018), who studied the effect of governance on the zakat distribution efficiency, Ryandono & Wijayanti (2019) studied the transformation of zakat institutions in empowering social entrepreneurs, and Mubtadi (2019) tried to define the Islamic Governance concept.…”
Section: The Governance Of Zakat Institutionmentioning
confidence: 99%
“…In addition, As cited in (Wahyuni, 2017), Buck et al also emphasized that the adequacy of human resources and capital inputs were considered as one important factor that determines the performance of a company or a firm. Moreover, the more appropriate labor hired strategy the more competitiveness a company has.…”
Section: Human Resource Adequacymentioning
confidence: 99%